2006 IEEE 63rd Vehicular Technology Conference
DOI: 10.1109/vetecs.2006.1682790
|View full text |Cite
|
Sign up to set email alerts
|

Uplink Performance Analysis for a Relay Based Cellular System

Abstract: Mobile cellular communication systems beyond third generation (3G) are expected to allow subscribers to access an unlimited amount of multimedia and/or voice data with a guaranteed quality of service (QoS) irrespective of their locations. There is therefore a general and continuing requirement to seek improvements to present cellular communication systems for the provisioning of greater throughput per subscriber. In this scope, a further portfolio of standards coined as fourth generation (4G) is currently unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…For direct path, by substituting P M into (5), the throughput can be obtained by (8). For a 2-hop path, again, t M →Rj ( m) = t R j →B ( m) gives the highest spectral efficiency.…”
Section: B Measure 2-maximization Of Uplink System Spectral Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…For direct path, by substituting P M into (5), the throughput can be obtained by (8). For a 2-hop path, again, t M →Rj ( m) = t R j →B ( m) gives the highest spectral efficiency.…”
Section: B Measure 2-maximization Of Uplink System Spectral Efficiencymentioning
confidence: 99%
“…There have been few studies on the uplink performance of the relay-assisted cellular systems [8]- [10]. In [8], the issues of capacity, cell coverage, and MS transmit power were considered in a relay-assisted CDMA network with six RSs under different frequency allocation methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both steps will require appropriate time/spectral resource allocation, which leads to a certain penalty to the overall link spectral efficiency. Previous works have shown that relay transmission can achieve higher spectral efficiency than direct transmission only if the direct source to destination link experiences much poorer fading condition than the relay links [6]. These results have, as such, generated considerable interest in opportunistic relaying systems [7].…”
Section: Introductionmentioning
confidence: 99%
“…We assume the mode selection is based on user location. Specifically, the service area is divided into two different coverage zones: the inner zone and the outer zone [6]. The inner zone is approximated by a circle with radius R bs while the outer zone by a ring with radius D − R bs , where D is the radius of the relay-enhanced cell.…”
Section: Introductionmentioning
confidence: 99%